Internalization-related host factors of common respiratory viruses - Lv, Qiuchi; Xie, Zhengde; Xu, Lili (Frontiers in Immunology, 2026)
Respiratory viruses impose a substantial health burden worldwide, with viral internalization into host cells being the initial step for infection establishment. This process is tightly regulated by the host cellular machinery through two major pathways: receptor-mediated endocytosis and direct membrane fusion. To clarify the role of host factors in these steps, we present human adenovirus and respiratory syncytial virus as representative non-enveloped and enveloped viruses, respectively, as models to elucidate their life cycles, focusing on how host factors mediate their distinct internalization processes. We further categorized the host factors involved in the internalization of other common respiratory viruses, including coronaviruses, influenza A virus, and human metapneumovirus. By analyzing the virus–host interaction mechanisms underlying these processes, this review provides critical insights for developing broad-spectrum antiviral therapies targeting conserved host factors that govern viral internalization.